Identification of potential complementary serum biomarkers to differentiate prostate cancer from benign prostatic hyperplasia using gel- and lectin-based proteomics analyses - Jayapalan, J.J.; Ng, K.L.; Razack, A.H.A.; Hashim, Onn Haji (2012)
Diagnosis of prostate cancer (PCa) is currently much reliant on the invasive and time-consuming transrectal ultrasound-guided biopsy of the prostate gland, particularly in light of the inefficient use of prostate-specific antigen as its biomarker. In the present study, we have profiled the sera of patients with PCa and benign prostatic hyperplasia (BPH) using the gel- and lectin-based proteomics methods and demonstrated the significant differential expression of apolipoprotein AII, complement C3 beta chain fragment, inter-alpha-trypsin inhibitor heavy chain 4 fragment, transthyretin, alpha-1-antitrypsin, and high molecular weight kininogen (light chain) between the two groups of patientsâ samples. Our data are suggestive of the potential use of the serum proteins as complementary biomarkers to effectively discriminate PCa from BPH, although this requires further extensive validation on clinically representative populations.